Development of Eco-friendly Antimicrobial Bricks Using Nickel Slag Waste Enriched with TiO2 to Counteract E. coli Contamination - L. Agusu; W. O. Nurtia; M. Z. Muzakkar; I W. Sutapa; Y. Ishikawa; Y. Fujii; T. Asano; S. Mitsudo; Y. Tatematsu (International Journal of Acta Material, 2025)
This study investigates the use of nickel slag waste, enriched with TiO2, as a sustainable material for producing antimicrobial bricks. The research focuses on evaluating the impact of variations in firing time and the addition of nickel slag on the mechanical properties of the bricks, as well as their antibacterial effectiveness against E. coli bacteria. The bricks were produced using an electric furnace with different composition ratios of clay, nickel slag, and TiO2. Results demonstrate that the optimal compressive strength of the bricks is 21.673 × 10⁵ N/m², achieved with a clay:slag:TiO2 ratio of 90:5:5 at a firing temperature of 1000°C for 12 hours. The water absorption rate for this composition was found to be 16.98%. Antimicrobial tests, using the scatter method, revealed that TiO2-enriched bricks significantly inhibited E. coli growth, with only two colonies present compared to 77 colonies on bricks without TiO2. X-ray diffraction (XRD) analysis confirmed the presence of key oxides such as SiO2, TiO2, and CaCO3. These findings suggest that nickel slag, when combined with TiO2, can be an effective additive in clay-based bricks to inhibit E. coli growth, offering potential for applications in water purification and environmental sustainability. Furthermore, the use of advanced heating techniques such as microwaves or gyrotrons may enhance the bricks’ structural integrity and antimicrobial performance in future applications.